2019
DOI: 10.3390/c5030047
|View full text |Cite
|
Sign up to set email alerts
|

Macadamia Nutshell Biochar for Nitrate Removal: Effect of Biochar Preparation and Process Parameters

Abstract: Agricultural runoff is a major cause of degradation to freshwater sources. Nitrate is of particular interest, due to the abundant use of nitrogen-based fertilizers in agricultural practices globally. This study investigated the nitrate removal of biochar produced from an agricultural waste product, macadamia nutshell (MBC). Kinetic experiments and structural analyses showed that MBC pyrolsed at 900 • C exhibited inferior NO 3 − removal compared to that pyrolsed at 1000 • C, which was subsequently used in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In a similar study on adsorption capabilities, Bakly et al (2019) reported nitrate removal with macadamia nutshell biochar from slow pyrolysis; more than 45% of nitrate was removed at the highest concentration and at the lowest flow rate. Bakly et al (2019) also attributed the adsorption capabilities to the biochar size, porosity, and surface area; the biochar samples were ground and sieved with a size range of 1.18 mm to 2.30 mm before adsorption testing. Furthermore, agricultural runoff is a major cause of degradation to freshwater sources, so the removal of nitrate content is a concern, due to the abundance of nitrogen-based fertilizers in agriculture (Bakly et al 2019).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In a similar study on adsorption capabilities, Bakly et al (2019) reported nitrate removal with macadamia nutshell biochar from slow pyrolysis; more than 45% of nitrate was removed at the highest concentration and at the lowest flow rate. Bakly et al (2019) also attributed the adsorption capabilities to the biochar size, porosity, and surface area; the biochar samples were ground and sieved with a size range of 1.18 mm to 2.30 mm before adsorption testing. Furthermore, agricultural runoff is a major cause of degradation to freshwater sources, so the removal of nitrate content is a concern, due to the abundance of nitrogen-based fertilizers in agriculture (Bakly et al 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Li et al (2019) reported microwave-pyrolysis biochar of Artemisia selengensis and its adsorption capacity for methylene blue, for which biochar pores, surface area, and pyrolysis conditions influenced the adsorption capabilities (Li et al 2019). In a similar study on adsorption capabilities, Bakly et al (2019) reported nitrate removal with macadamia nutshell biochar from slow pyrolysis; more than 45% of nitrate was removed at the highest concentration and at the lowest flow rate. Bakly et al (2019) also attributed the adsorption capabilities to the biochar size, porosity, and surface area; the biochar samples were ground and sieved with a size range of 1.18 mm to 2.30 mm before adsorption testing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Beck et al (2011) also showed that adding biochar to green roof trays increased nitrate retention. The retention of nitrate onto biochar could be attributed to the electrochemical interaction and binding with the functional groups (Bakly et al, 2019). Steam activation of biochar almost doubled the positive effects of biochars for nutrient retention, and this highlights the need for further investigation for effective application of biochar in hydroponic systems (Borchard et al, 2012).…”
Section: Biochar Impact On Nitrate Concentrationmentioning
confidence: 99%
“…In addition, Macadamia nutshell is used to produce biomass pyrolysis through controlled high-temperature serial reactions ( Poinern et al, 2011 ). Several pyrolysis-based biochar applications include steel production ( Kumar et al, 2017 ), soil amendments ( Wrobel-Tobiszewska et al, 2018 ), and de-nitrification mechanism ( Bakly et al, 2019 ). Similarly, the nutshells of almond, hazelnut, walnut, and apricot are a cost-effective source of activated carbons for treatment of industrial effluents ( Aygün et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%